THEORETICAL ASPECTS OF SOCIALIZATION OFFICIALS OF THE INTERNAL AFFAIRS PROCESS OF PROFESSIONAL CULTURE FORMATION - I. Mykhaylichenko (Academy of Cognitive and Natural Sciences, 2002)
The theoretical bases of socialization of workman's of organs o f internal deals are considered in the article as factors of shaping the professional culture.